2020
DOI: 10.3390/ijms21103593
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Effective Flow Cytometry-Based Method for Identification and Quantification of Tissue Infiltrated Leukocyte Subpopulations in a Mouse Model of Peripheral Arterial Disease

Abstract: Arteriogenesis, the growth of a natural bypass from pre-existing arteriolar collaterals, is an endogenous mechanism to compensate for the loss of an artery. Mechanistically, this process relies on a locally and temporally restricted perivascular infiltration of leukocyte subpopulations, which mediate arteriogenesis by supplying growth factors and cytokines. Currently, the state-of-the-art method to identify and quantify these leukocyte subpopulations in mouse models is immunohistology. However, this is a time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Secondly, M2-like polarized regenerative macrophages, which are identifiable through the presence of MRC1 [ 21 , 22 ]. Analyzing spatial and temporal macrophage dynamics revealed that the magnitude of arteriogenesis is directly proportional to the optimal balance of M1-like and M2-like macrophages [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, M2-like polarized regenerative macrophages, which are identifiable through the presence of MRC1 [ 21 , 22 ]. Analyzing spatial and temporal macrophage dynamics revealed that the magnitude of arteriogenesis is directly proportional to the optimal balance of M1-like and M2-like macrophages [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arteriogenesis was induced by femoral artery ligation (FAL) according to the previously published protocol [ 23 , 32 ]. Briefly, after anesthetizing mice with a standard combination of fentanyl (0.05 mg/kg; CuraMED, Karlsruhe, Germany), midazolam (5.0 mg/kg; Ratiopharm, Ulm, Germany), and medetomidine (0.5 mg/kg; Pfister Pharma, Berlin, Germany), the skin of the upper thigh on both limbs was disinfected, and hair from the surgical site was shaved.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were sacrificed 7 days after HLI surgery by means of CO2 and perfused with 10 ml of cold PBS. Surface adductors were dissected as previously described 86 and collected in cold DMEM. Next, adductor muscles were diced and digested in 0.1% collagenase IV (C5138, Sigma) for 45 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Co-workers of the group of Elisabeth Deindl describe the functional role of extracellular RNA in that process and highlight the role of this nucleic acid during ongoing arteriogenesis [3]. Moreover, the same group presents a simple flow cytometry-based method to identify and quantify tissue infiltrated leukocyte subpopulations [4]. Macrophages, which accumulate in the perivascular tissue of growing collateral arteries, are well described for their pro-arteriogenic feature.…”
mentioning
confidence: 99%